2020
DOI: 10.1093/mnras/staa1667
|View full text |Cite
|
Sign up to set email alerts
|

Blue straggler populations of seven open clusters with Gaia DR2

Abstract: ABSTRACT Blue straggler stars (BSS) are well studied in globular clusters but their systematic study with secure membership determination is lacking in open clusters. We use Gaia DR2 data to determine accurate stellar membership for four intermediate-age open clusters, namely Melotte 66, NGC 2158, NGC 2506, and NGC 6819, and three old open clusters, namely, Berkeley 39, NGC 188, and NGC 6791, to subsequently study their BSS populations. The BSS radial distributio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 71 publications
1
20
0
1
Order By: Relevance
“…However, there are cases such as NGC 2477, whose AL07 BSS are all members, but that appear concentrated around the TO and sub-giant branch in the Gaia CMD. On the other hand, for close and very well studied clusters with spectroscopically confirmed BSS, it is possible to retrieve about 70% and in some cases up to 100%, as Vaidya et al (2020) have demonstrated. We are aware that some BSS are lost given our stringent and conservative selection criteria.…”
Section: Comparison With Al95 and Al07mentioning
confidence: 73%
“…However, there are cases such as NGC 2477, whose AL07 BSS are all members, but that appear concentrated around the TO and sub-giant branch in the Gaia CMD. On the other hand, for close and very well studied clusters with spectroscopically confirmed BSS, it is possible to retrieve about 70% and in some cases up to 100%, as Vaidya et al (2020) have demonstrated. We are aware that some BSS are lost given our stringent and conservative selection criteria.…”
Section: Comparison With Al95 and Al07mentioning
confidence: 73%
“…Bhattacharya et al 2017b), as well as through the radial distribution of massive objects, such as blue stragglers (e.g. Bhattacharya et al 2019;Vaidya et al 2020;Rao et al 2021). Alongside this internal effect, Galactic potential perturbs star clusters leading to the formation of tidal structures.…”
Section: Introductionmentioning
confidence: 99%
“…Our method for assessing membership using proper motions and parallaxes from Gaia DR2 decreases, but does not remove all the contamination by such field young stars. To do so, and following Vaidya et al (2020), we limited each cluster's radius to that at which there are more cluster stars than field stars. We estimated the cluster size as the radius R where the cluster density profile sepa- 3.…”
Section: Field Contaminationmentioning
confidence: 99%
“…Finally, in the Family III class of GCs, the external maximum disappears, and the only noticeable peak in the distribution is the central one, followed by a minimum. A similar work in open clusters has been carried out by Vaidya et al (2020). The authors determined accurate stellar membership and studied the BS radial distribution on seven open clusters.…”
Section: Introductionmentioning
confidence: 97%